Novos finais felizes: a mulher e o casamento em Ana Maria Machado, Ruth Rocha e Sylvia Orthof - Villaça, Maria Cristina Conduru (2004)
The aim of this project is to point out the importance of fairy tales as documents for social and cultural research. Reflecting about the view we go for comprehending their transformations. The dynamic nature of these stories allows adaptations and readings that make them suitable to the Historic context they are connected to. Women representation and marriage dimension, connected to the happiness myth, come across that dynamism, being modified along times. Contemporary authors search new happy endings when they try to compact to new values. We try to confirm the importance of Ana Maria Machado, Ruth Rocha and Sylvia Orthof as significant names of new literature for Brazilian young people.